Here's the dirt: First applications of confocal microscopy for quantifying microwear on experimental ground stone earth working tools. (August 2019) - Macdonald, Danielle A.; Xie, Liye; Gallo, Tiziana
Abstract: Quantitative microscopy characterizing the surface texture of wear traces has helped develop a more standardized chipped stone tool microwear practice. However, to date, these surface metrology methods have not been used to characterize ground stone tool surfaces. To expand the range of raw materials and tool types tested with these methods, we explore the application of imaging confocal microscopy for the quantification of an assemblage of experimental hoes, modelled after Late Neolithic and Early Bronze Age artifacts from China. Surface texture properties of sediment wear are compared to wear from wooden hafts to identify whether confocal microscopy can distinguish between different wear types. The results show that there is a significant difference between sediment and hafting wear and suggests further research is needed to identify how experimental conditions affect polish measurements within wear types. This preliminary study indicates that imaging confocal microscopy has excellent potential for the quantification of microwear traces on ground stone tools and may contribute to our understanding of earth working tools in prehistory. Highlights: Confocal microscopy is used to distinguish between different polish types on ground stone digging tools. There are measurable differences in polish surface texture between sediment polish and wood hafting polish. Surface quantification using confocal microscopy is a new method that can be used for ground stone tool microwear analysis.